Distribuição de combustíveis no estado de São Paulo: estruturas de governança e oportunismo - Soares, Selene de Souza Siqueira (Universidade Federal de São Carlos, 2012)
This work is directed to the study of transactions governance adopted by fuel distributors in the State of Sao Paulo with retail market sellers or gas stations. The applied theoretical approach lies on studies of New Institutional Economics, favoring the study of Transaction Costs Economics, using attributes of transactions defined by Williansom (1979) and other studies by authors such as Ménard (2001, 2004; 2006) which emphasizes hybrids coordination devices complementary to contracts such as influence, leadership, confidence and ad hoc institutions. The supply sector study under this theoretical point of view is quite interesting, because since the begging of deregulation process in the late 1990s, the final link in this chain has brought distinct governance. Two kinds of transactions keep going on simultaneously: sales in the spot market among all distributors and no branded gas station (or so called white flag resellers), and hybrid governance structures with long-term contracts between distributors and their gas station franchisees. This has been a common strategy adopted by dominant distributors and pursued in some extent by regional distributors. In addition, the observation of governance in the sector progressively highlights the representativeness of opportunistic behavior, especially those related to fuel adulteration and acquisitions outside the exclusive arrangement of negotiations. The control decisions of such opportunistic behavior and recognition of their impact in the coordination of transactions have become essential for understanding the expected stability in this governance and their suitability as minimizing structures of transaction costs. The results of this thesis suggest that the governance structures of the transactions differ by asset specificity. Hybrid governance structure is the most common one. The control of opportunistic actions in this kind of structure has been carried out by using contractual mechanisms and complementary mechanisms to contracts. On the other side, regional distributors set transactions of lower asset specificity and use influence as the only coordinating mechanism complementary to those contracts. However, in terms of business share, transactions through market are still the most frequent ones in this segment. As for the third group of distributors, the independent ones, transactions take place uniquely through the market and the control of opportunistic actions are dispensed by them and transferred to sectorial monitoring public organizations. Delay in asserting the contracts has been the main cause of the uprising of complementary mechanisms, and its utilization has been directed basically to the protection of the specific assets in transactions, specially in the preservation of the unique trading channels, recovery of specific investments and mainly to protect its brand-specific assets. If, in one hand, the hybrid governance efficiency in the use of these mechanisms enhances the transaction costs and approaches to governance structure of hierarchical and centralised structures, on the other hand, in low asset specific transactions, relations of spot market and competitive bases of another thread are consolidated differently from the first, looking primarily for lower prices despite the appeal of quality referenced by the main specific distributors firms assets distributors: their brands.
Keywords: Economia institucional; Estruturas de governança; Combustível - distribuição; Álcool; Gasolina; ENGENHARIAS::ENGENHARIA DE PRODUCAO